INTELLIGENCE – MILITARY SECURITY OF AMIR TEMUR SALTANAT AN IMPORTANT TOOL IN PROVIDING (Web of Teachers: Inderscience Research, 2025)
This article comparatively analyzes the role and importance of the internal intelligence service in ensuring military security during the reign of Amir Temur, its official activities and functional responsibilities, as well as the organizational structure of the internal intelligence service and is highlighted on the basis of historical sources.